Implementasi Nilai-Nilai Pendidikan Demokrasi Pada Siswa Kelas VIII SMP Negeri 1 Situraja - Serlina Agustin; Dinie Anggraeni Dewi (Journal on Education, 2021)
This research aims to determine the form of implementation of the values of democracy education in grade VIII students of SMP Negeri 1 Situraja. The research method used is a case study method with a qualitative approach. The research informants were class VIII students of SMP Negeri 1 Situraja in the 2020/2021 school year with data collection techniques, namely asynchronously using google form media. The results showed that the values of democracy which became the benchmark in developing democracy had been lived by students, especially in grade VIII students of SMP Negeri 1 Situraja. They have implemented democratic values in the school environment. The values of democratic education are tolerance, honesty, social spirit, environmental care, creativity and responsibility. These democratic values are implemented through activities organized by the OSIS at SMP Negeri 1 Situraja.